Peran Kewarganegaraan Digital dalam Perspektif Hukum Islam bagi Muslim di Dunia Maya - Ahmad Muhamad Mustain Nasoha; Ashfiya Nur Atqiya; Tya Nur Ramadani; Widya Nur Hidayah; Elok Salmah Nasicha (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
In the current digital era, technological advances have brought considerable changes, which can be seen in the way individuals gather information, interact, and play an active role in social life. The concept of citizenship is no longer limited to the physical world, but has expanded to the digital. In the digital sphere, everyone has rights and obligations, including maintaining communication ethics, protecting personal privacy and others, and taking part in more positive activities. As in the Islamic view, in the digital world, people must always participate and be based on sharia principles, such as honesty, responsibility, and respect for the rights of others. This study aims to examine the role of digital citizenship in the perspective of Islamic law, which uses a qualitative approach and normative analysis. The results of this study also show that there are several aspects that are influential in the digital era such as the importance of protecting personal data as part of the main objective of sharia, maintaining communication ethics by prioritizing the principles of politeness and honesty, and preventing the spread of hoax information. Islam also strongly emphasizes the importance of hate speech and bullying among virtual communities. In addition, freedom of expression in the digital sphere must be accompanied by moral responsibility to anticipate conflicts.With this understanding, Muslims are expected to contribute to creating a digital space that is safer, healthier, harmonious, and in accordance with sharia teachings